1998
DOI: 10.1007/bf02267786
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of oral salt on plasma volume, orthostatic tolerance, and baroreceptor sensitivity in patients with syncope

Abstract: Salt loading of patients with orthostatic-related syncope has been shown to increase plasma volume and orthostatic tolerance and to decrease baroreceptor sensitivity. This study aims to define the time course of these changes and reveal indications as to the likely mechanisms involved. We measured plasma volume by Evans blue dilution, orthostatic tolerance by time to presyncope in a test of combined head-up tilt and lower body suction, and baroreceptor sensitivity as the cardiac interval prolongation to neck s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 17 publications
2
56
0
Order By: Relevance
“…increased dietary salt/electrolyte intake with fluids such as 'sport' drinks, salt tablets) or moderate exercise training [269][270][271][272] appear to be among the safest initial approaches (level B). Additionally, in highly motivated patients with recurrent vasovagal symptoms, the prescription of progressively prolonged periods of enforced upright posture (so-called 'tilt-training') may reduce syncope recurrence [273,274] (level B).…”
Section: Vasovagal Syncopementioning
confidence: 99%
“…increased dietary salt/electrolyte intake with fluids such as 'sport' drinks, salt tablets) or moderate exercise training [269][270][271][272] appear to be among the safest initial approaches (level B). Additionally, in highly motivated patients with recurrent vasovagal symptoms, the prescription of progressively prolonged periods of enforced upright posture (so-called 'tilt-training') may reduce syncope recurrence [273,274] (level B).…”
Section: Vasovagal Syncopementioning
confidence: 99%
“…6,71 Similarly, expansion of plasma volume following salt supplementation improves orthostatic tolerance. 72,73 Thus, it would be expected that salt depletion and/or small plasma volumes would predispose to orthostatic hypotension. 66 In patients with chronic SCI, there is evidence of impaired water and sodium retention in the seated position, and limited salt and water intake.…”
Section: Altered Salt and Water Balancementioning
confidence: 99%
“…Advice and avoidance of precipitating factors 87,90,91 Increased salt and fluid intake 48,72 Abdominal compression bandages and/or support stockings 87,90,91 Sleeping with the bed head raised by 10-201 80,92 Minimize postprandial hypotension 87,90,91 Pharmacotherapy Fludrocortisone 92,93 Midodrine 94,95 Nonpharmacological measures should form the first line of therapy following SCI are unclear, but are likely to be multifactorial. Some possible contributing factors are lack of tonic sympathetic control (particularly in those with high level lesions), impaired baroreceptor regulation, lack of skeletal muscle pumping activity in the dependant limbs of paralysed individuals, cardiovascular deconditioning following prolonged periods of bed rest and hyponatremia with the resultant hypovolemia.…”
Section: Nonpharmacological Managementmentioning
confidence: 99%
“…This was associated with a significant increase in the maximal forearm vasoconstriction from 64.4%Ϯ13.7% (SEM) Key Words: sodium Ⅲ vascular resistance P revious work from our laboratory, including a doubleblind placebo-controlled trial, has demonstrated that salt supplementation improves orthostatic tolerance in patients with posturally related syncope (PRS). [1][2][3] This increase in tolerance to orthostatic stress was attributed partly to increases in plasma volume 1 and partly to increased baroreceptor sensitivity. 3 We have also shown that the increase in vascular resistance in response to an orthostatic stress is significantly smaller in patients with poor orthostatic control than in healthy volunteers.…”
mentioning
confidence: 99%
“…[1][2][3] This increase in tolerance to orthostatic stress was attributed partly to increases in plasma volume 1 and partly to increased baroreceptor sensitivity. 3 We have also shown that the increase in vascular resistance in response to an orthostatic stress is significantly smaller in patients with poor orthostatic control than in healthy volunteers.…”
mentioning
confidence: 99%